Investigations on the Aetiology and Antibiotic Management of Neonatal Septicemia - Hans Eldih Monintja (Indonesian Pediatric Society, 1988)
This is a prospective study aimed in identifying the latest aetiological factors of neonatal sepsis in Dr. Cipto General Hospital, Jakarta, and investigating the efficacy of antibiotics treatment especially with ceftriaxone. This study revealed that the present main causative microorganisms are as follows: Pseudomonas, Klebsiella and E. coli. The case fatality rates being: (1) Standard treatment with ampicillin and gentamycin: 80.9%, (2) S(andard treatment with consomittant ceftriaxone: 20%, (3) Ceftriaxone: 9,52%. It seems that in facing neonatal septicemia, the initial antibiotic should be the third generation cephalosporine. The second choice is chloramphenicol. However, the causative agent and the sensitivity test should be monitored regularly.